Improvement of SNR and acquisition acceleration using a 32-channel head coil compared to a 12-channel head coil at 3T. (July 2013) - Reiss-Zimmermann, Martin; Gutberlet, Marcel; Köstler, Herbert; Fritzsch, Dominik; Hoffmann, Karl-Titus
Background: Magnetic resonance imaging (MRI) techniques continue to improve in manifold ways. Besides field strength and sequence optimization, technical advances in coil design and sensitivity yield to increase the signal detection and therefore improve image quality. Purpose: To evaluate the performance of signal-to-noise ratio (SNR) and parallel acquisition technique (PAT) acceleration of a dedicated 32-channel head coil compared with a standard 12-channel head coil. Material and Methods: In a clinical 3T setting, spatial resolved SNR values for unaccelerated imaging and PAT with acceleration factors of 2–6 of a 32-channel head coil were evaluated in relation to a 12-channel head coil. SNR was determined quantitatively using proton-density-weighted in-vivo examinations in five healthy volunteers. Quantitative SNR maps for unaccelerated and PAT imaging were calculated using unfiltered MR raw data. Results: Up to three-fold higher SNR values were achieved with the 32-channel head coil, which diminished towards the center to an increase of 40% compared with the 12-channel head coil. When using PAT, the 32-channel head coil resulted in a lower spatial-dependent quantitative noise enhancement, varying between 0% at R = 2 and 33% at R = 5. Conclusion: The 32-channel head coil provided superior SNR both with and without PAT compared with a 12-channel head coil, especially close to the brain surface. Using PAT, the unavoidable noise enhancement is diminished up to acceleration factors of 6 for the 32-channel head coil. Therefore, the 32-channel head coil is considered as a preferable tool for high-resolution neuroradiological imaging.